2020
DOI: 10.1021/acsomega.0c03173
|View full text |Cite
|
Sign up to set email alerts
|

Spatially and Temporally Resolved Heterogeneities in a Miscible Polymer Blend

Abstract: Mapping the spatial and temporal heterogeneities in miscible polymer blends is critical for understanding and further improving their material properties. However, a complete picture on the heterogeneous dynamics is often obscured in ensemble measurements. Herein, the spatial and temporal heterogeneities in fully miscible polystyrene/oligostyrene blend films are investigated by monitoring the rotational diffusion of embedded individual probe molecules using defocused wide-field fluorescence microscopy. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It is observed that most fluorescent molecules are of doublelobe-shaped pattern, indicating their spatial orientation parallel to the film surface, with a small portion having the out-of-plane orientation. [18,21,27,[30][31][32][33] The videos recorded at different temperatures show that with the increase of temperature, more and more fluorescent molecules rotate and their rotating angle becomes larger. Dynamical heterogeneity is also clearly observed -the rotational rate of fluorescent molecules differs for probes at different locations and that of the same fluorescent molecule changes with time.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that most fluorescent molecules are of doublelobe-shaped pattern, indicating their spatial orientation parallel to the film surface, with a small portion having the out-of-plane orientation. [18,21,27,[30][31][32][33] The videos recorded at different temperatures show that with the increase of temperature, more and more fluorescent molecules rotate and their rotating angle becomes larger. Dynamical heterogeneity is also clearly observed -the rotational rate of fluorescent molecules differs for probes at different locations and that of the same fluorescent molecule changes with time.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation rotational time τ c could be calculated by τc=(τKWW/0ptτKWWβKWWβKWW)·normalΓ(1/1β0.0ptβKWW)${\tau _{\mathrm{c}}} = ( {{{{\tau _{{\mathrm{KWW}}}}} \mathord{/ {\vphantom {{{\tau _{{\mathrm{KWW}}}}} {{\beta _{{\mathrm{KWW}}}}}}} \kern-\nulldelimiterspace} {{\beta _{{\mathrm{KWW}}}}}}} ) \cdot \Gamma ( {{{{1 \mathord{/ {\vphantom {1 \beta }} \kern-\nulldelimiterspace} \beta }}_{{\mathrm{KWW}}}}} )$, where Γ denotes a gamma function. [ 26,45 ]…”
Section: Methodsmentioning
confidence: 99%
“…The correlation rotational time 𝜏 c could be calculated by 𝜏 c = (𝜏 KWW ∕𝛽 KWW ) ⋅ Γ(1∕𝛽 KWW ), where Γ denotes a gamma function. [26,45] The preciseness of measurement of the dynamics by doped fluorescent probe was depended on the length of rotation trajectory and the characteristic relaxation time varied with the trajectory length. Considering the existence of dynamic heterogeneity with a broad distribution of relaxation time, an alternative approach was to conduct analysis in the frequency domain, i.e., the power spectrum analysis.…”
Section: Single Molecule Defocused Fluorescence Microscopymentioning
confidence: 99%